Visual Detection of Duck Tembusu Virus With CRISPR/Cas13: A Sensitive and Specific Point-of-Care Detection - Yin, Dongdong; Yin, Lei; Wang, Jieru; Shen, Xuehuai; Pan, Xiaocheng; Hou, Hongyan; Zhao, Ruihong; Hu, Xiaomiao; Wang, Guijun; Qi, Kezong; Dai, Yin (Frontiers in Cellular and Infection Microbiology, 2022)
Duck tembusu virus (DTMUV), which causes huge economic losses for the poultry industries in Southeast Asia and China, was first identified in 2010. DTMUV disease has become an important disease that endangers the duck industry. A sensitive, accurate, and convenient DTMUV detection method is an important means to reduce the occurrence of the disease. In this study, a CRISPR/Cas13a system was combined with recombinase polymerase amplification to develop a convenient diagnostic method to detect DTMUV. The novel method was based on isothermal detection at 37°C, and the detection was used for visual readout or real-time analysis. The assay was highly sensitive and specific, with a detection limit of 1 copy/μL of the target gene and showed no cross-reactivity with other pathogens. The enhanced Cas13a detection worked well with clinical samples. Overall, a visual, sensitive, and specific nucleic acid detection method based on CRISPR/Cas13a proved to be a powerful tool for detecting DTMUV.